Analysis of the Effect of Service Provision and Consumer Motivation on Consumer Purchases in Phone Store (Case Study on Metta Cell Denai) - Cherry Cherry; August Halomoan Siregar (Jurnal Mantik, 2022)
This study aims to determine the effect of services and motivation on purchase decision of Metta Cell. This type of research is explanatory research. The population in this study were all consumers of Metta Cell during the 2020 period, totaling 9,351 consumers. The sampling technique used is the Slovin technique with an error tolerance of 10% so that as many as 99 samples are obtained. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that services and motivation partially or simultaneously have a positive and significant effect on purchase decision of Metta Cell. Based on the results of this study, the implications for management are to further improve services and motivation.